Detection of Multiple Lineages of PRRSV in Breeding and Growing Swine Farms - Cheng, Ting-Yu; Campler, Magnus R.; Schroeder, Declan C.; Yang, My; Mor, Sunil K.; Ferreira, Juliana B.; Arruda, Andréia G. (Frontiers in Veterinary Science, 2022)
The detection and co-circulation of multiple variants of porcine reproductive and respiratory syndrome virus (PRRSV) have been observed and reported in swine. However, the potential long-term impact of multiple prevailing PRRSV variants on pig-performance is not yet fully understood. The primary objective of this study was to describe the genetic variation of PRRSV in processing fluid (PF), oral fluid (OF), and tonsil scraping (TS) specimens from five swine farms with different production types and PRRS status over a period of time (~1 year). Furthermore, the association between PRRSV prevalence and production parameters was investigated. Results showed that PRRSV was detected by RT-qPCR in 21–25% of all types of specimens. In breeding farms, PRRSV detection in PF and/or TS samples was correlated with stillborn and mummified fetuses, and pre-weaning mortality throughout the study period. Although ORF5 sequences were obtained in <16% of all sample types, simultaneous detection of PRRSV variants including field and vaccine strains within a single sampling event was identified in both breeding and growing pig farms. Phylogenetic analyses based on the ORF5 sequence classified the detected field PRRSV into L1A and L1H, two sub-lineages of lineage 1 (L1). Our study demonstrated the presence of multiple PRRSV lineages, sub-lineages, and variants in swine herds and its potential association with swine reproductive performance under field conditions.